2010
DOI: 10.4137/vrt.s975
|View full text |Cite
|
Sign up to set email alerts
|

Intrabody-based Mapping of Latency-associated Nuclear Antigen from Kaposi's Sarcoma-associated Herpesvirus Show Conserved Epitopes for Viral Latency Inhibition

Abstract: Kaposi's sarcoma associated herpesvirus (KSHV or human herpesvirus 8 [HHV-8]) is a gammaherpesvirus highly associated with KS, primary effusion lymphoma (PEL), and multicentric Castleman's disease, an aggressive lymphoproliferative disorder. KSHV, like other gammaherpesvirus latently infects predominantly B-cells and endothelial cells. Infected cells retain the virus from one generation to the next existing as a multicopy circular episomal DNA in the nucleus, expressing a limited subset of viral genes. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Since the more public Abs against the immunodominant epitopes and discriminative peptides identified in this study mainly target intracellular proteins (LANA) or intracellular domains of membrane proteins (K15), they are unlikely to impart neutralizing activity. However, intrabodies–Abs expressed intracellularly–have been considered as therapeutics for infectious diseases and cancers [ 42 , 43 ], and intrabodies specific to KSHV LANA and vIL-6 have demonstrated some pre-clinical therapeutic potential [ 44 46 ]. Additionally, non-neutralizing Abs have been shown to provide protection against other viral infections [ 47 ], and although we have previously reported that the Ab-dependent cell cytotoxicity (ADCC) activity of plasma-derived Abs was not differential between KS and ASY, ADCC-mediating Abs have been detected in KSHV seropositive individuals, and it is possible that NK cell functional differentials may exist between KS and ASY and could target certain anti-KSHV repertoires better than others [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the more public Abs against the immunodominant epitopes and discriminative peptides identified in this study mainly target intracellular proteins (LANA) or intracellular domains of membrane proteins (K15), they are unlikely to impart neutralizing activity. However, intrabodies–Abs expressed intracellularly–have been considered as therapeutics for infectious diseases and cancers [ 42 , 43 ], and intrabodies specific to KSHV LANA and vIL-6 have demonstrated some pre-clinical therapeutic potential [ 44 46 ]. Additionally, non-neutralizing Abs have been shown to provide protection against other viral infections [ 47 ], and although we have previously reported that the Ab-dependent cell cytotoxicity (ADCC) activity of plasma-derived Abs was not differential between KS and ASY, ADCC-mediating Abs have been detected in KSHV seropositive individuals, and it is possible that NK cell functional differentials may exist between KS and ASY and could target certain anti-KSHV repertoires better than others [ 22 ].…”
Section: Discussionmentioning
confidence: 99%